Studi Literatur: Pelaksanaan Promotif dan Preventif Upaya Program Kesehatan Jiwa pada Puskesmas di Indonesia - Patricia Lydia Honey Patricia; Chriswardani Suryawati; Rani Tiyas Budiyanti (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2020)
Background: Mental health is still a complex problem that has received special attention from all over the world, including in Indonesia. The number of cases that increases causes a decrease in community productivity. The Community Health Center as a health service provider has the main function of promoting promotional and preventive efforts to improve mental health services in the community. Objectives: This study aims to analyze the implementation of promotional and preventive mental health efforts at community health centers from the elements of health human resources, the methods used and the facilities / infrastructure. Research Metodes: This research is a research that uses simplified approach systematic literatur review. The literature searches used included Science Direct, Pubmed, SpringerLink and Google Scholar Literature with predefined keywords and inclusion and exclusion criteria. Results: The results showed that the implementation of promotional and preventive mental health efforts in Indonesia was different from abroad in the level of development. The implementation of mental health efforts at community health centers in Indonesia has been running well but has not been maximized because the lack of family knowledge, adequate facilities and infrastructure so that training is needed for mental health village workers and nurses in empowering the community. Conclusion: The importance of the role and support of all parties, especially mental health cadres and community empowerment in the implementation of mental health program promotion and prevention efforts by the community health center. The availability of adequate and competent health personnel supports the effectiveness of mental health programs. The implementation mechanism according to the time and work program is an important priority. In addition, adequate facilities and infrastructure are also a measure of the success of programs.